IgA LINEAR BULLOUS DERMATOSIS IN CHILDHOOD. - Ivelina Yordanova; Valentin Valtchev; Dimitar Gospodinov; Snejina Vassileva (Peytchinski Publishing, 2015)
IgA linear bullous dermatosis, also known as chronic bullous dermatosis of childhood, is an autoimmune disease which may be idiopathic or drug-induced. The disease affects children and adults. We present a 4 years old girl with itchy polymorphic eruptions. The skin rash was presented by bullous-erosive rosette-like lesions with reddish-brown crust in the center, distributed on the skin of the face, trunk and extremities. The vesicles were filled with serous and hemorrhagic content. Laboratory examinations were within normal values according the age. Histopathological examination of the lesional skin revealed sub epidermal blister. Direct immunofluorescence of perilesional skin demonstrated linear deposition of IgA in the basement membrane. Systemic treatment with Methylprednisolon and Claritromycin was applied with satisfactory effect. The patient is under observation.